ANALISIS STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Ahmad Syamsu Lutfi; Sulistyorini; Chusnul Chotimah (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
This journal describes "Analysis of Principal Strategies in Improving Education Quality". The implementation of strategic management carried out by a school principal is an important thing that must be implemented so that educational institutions have a direction and innovation to achieve the desired goals effectively and efficiently. Therefore it is necessary to have an analysis that must be taken in deciding a strategy. The focus of discussion in this journal is; 1) The concept of educational strategic management, 2) Criteria and strategic management techniques, 3) Standards for improving the quality of education, 4) Analysis of the Principal's Strategy in improving the quality of education. The purpose of writing this scientific journal is; 1) Knowing the concept of strategic management, 2) Knowing the criteria and techniques of strategic management, 3) Knowing the standards for improving the quality of education, 4) Knowing the analysis and strategic role of school principals in improving the quality of education. This journal uses the method of library analysis, namely by utilizing library resources to obtain theories and limiting activities only to library collection materials and other factual references..